Optimalisasi Literasi Anak Melalui Program Membaca Buku Nyaring (Read Aloud) Pada Peserta Didik TK dan SD di Desa Ekas Buana - Nila Kartika Hakim; Nur Hayani Ramdhani; Nila Sahara; Kelvin Harianto; Adim Rizman; Lalu Wahyu Andi Purnama (BALE LITERASI, 2026)
Low reading interest and limited basic literacy skills among early childhood and primary school-aged children remain challenges in various regions, including Ekas Buana Village, East Lombok Regency. This situation is influenced by a lack of early reading habits and the increasing use of mobile phones for entertainment. One strategy to improve children's literacy is through